Peningkatan Kualitas Lembaga Pendidikan Melalui Pendekatan Lean Six Sigma - Durrotul Masruroh (https://ejournal.insuriponorogo.ac.id/, 2023)
Improving the quality of Islamic educational institutions needs to continue to be pursued by prioritizing the theory of quality analysis and its application in every managerial process. But in reality, the problems faced by Islamic educational institutions are so diverse. Starting from management problems, leadership problems, human resources, finance, and institutional problems. This study aims to examine